2017
DOI: 10.1590/1678-69712017/administracao.v18n5p92-115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management Practices on Job Satisfaction

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. ALICIA OMARUniversidad Nacional de Rosario (UNR), Rosario -Santa Fe, Argentina. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
2
10
0
11
Order By: Relevance
“…Besides, Sanger (2013) conduct a study on employees of High Court, North Sulawesi, and founds that work motivation, job involvement, and performance appraisal have instantaneously and comparatively correlated with the satisfaction of employees. Numerous earlier studies evidenced that HRMPs predicted higher performance, motivational level, and satisfaction level of employees at the workplace that further produce positive outcomes (Abdirahman et al, 2018;Chukwuka & Nwakoby, 2018;Hee & Jing, 2018;Islam et al, 2018;Khoreva & Wechtler, 2018;Madanat & Khasawneh, 2018;Octaviannand et al, 2017;Omar et al, 2017). As reported by Koedel et al (2017), HRMPs are part of job satisfaction, which becomes the cause of an increase in employee performance.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 92%
“…Besides, Sanger (2013) conduct a study on employees of High Court, North Sulawesi, and founds that work motivation, job involvement, and performance appraisal have instantaneously and comparatively correlated with the satisfaction of employees. Numerous earlier studies evidenced that HRMPs predicted higher performance, motivational level, and satisfaction level of employees at the workplace that further produce positive outcomes (Abdirahman et al, 2018;Chukwuka & Nwakoby, 2018;Hee & Jing, 2018;Islam et al, 2018;Khoreva & Wechtler, 2018;Madanat & Khasawneh, 2018;Octaviannand et al, 2017;Omar et al, 2017). As reported by Koedel et al (2017), HRMPs are part of job satisfaction, which becomes the cause of an increase in employee performance.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 92%
“…In addition, the company also provides indirect compensation for adequate health and welfare facilities to support the lives of operators and their families. According to JICA and Omar employees are permitted to have side jobs, health care benefits, and well-developed pension plans [33][34]. Almeida also believes the improvement of recreational facilities, health allowances, subsidized loans, canteens, safety, housing, work equipment, etc.…”
Section: A Compensationmentioning
confidence: 99%
“…Omar, A., Salessi, S., & Urteaga, F. (2017) in their study stated that the type of human resource management is of crucial importance regarding the development of attitudes related to work, such as job satisfaction. Job satisfaction is a desirable outcome of many initiatives and processes of the firm [22]. Ashita Bhagra and Dinesh Kumar Sharma (2018) in their study concluded that today technological innovations are affecting the skills requirements at the job like never before.…”
Section: Literature Surveymentioning
confidence: 99%